Decentralization, pro-poor land policies, and democratic governance - Meinzen-Dick, Ruth S.; Gregorio, Monica Di; Dohrn, Stephan (International Food Policy Research Institute, 2008)
Decentralized approaches to development are gaining increasing prominence. Land tenure reform policy has been affected by many different types of decentralization. However, the literature on land tenure reform rarely explicitly addressed the implications of decentralization, and vice versa. This paper provides a review of how the issues of decentralization are linked to land tenure reform, in theory and practice. Both decentralization and land tenure reform each encompass a number of different, but related concepts and approaches. We begin with clarifying some key terms related to these different approaches, then look in more detail at contending perspectives on decentralization, and how these relate to the United Nations Development Programme's (UNDP) pillars of democratic governance. We then review the different types of land tenure reform in terms of the role of centralized and decentralized institutions, illustrating the strengths and weaknesses, gaps and challenges with experience from a range of developing countries. The final section turns to conclusions and policy recommendations, considering how decentralized approaches to land tenure reform can contribute to goals such as gender equity, social cohesion, human rights, and the identity of indigenous peoples.